2019
DOI: 10.1002/ncp.10430
|View full text |Cite
|
Sign up to set email alerts
|

Seven Deadly Sins of Nutrition Therapy in Critically Ill Patients

Abstract: This article presents 7 nutrition steps that, if not followed by the clinical staff, may be metaphorically considered as “7 deadly sins” of nutrition therapy. In this review, we suggest approaches that must be avoided or accomplished to increase compliance with the “Ten Commandments” of good nutrition practice in the intensive care setting. Multiple aggressive and simultaneous sets of therapies are implemented in the intensive care setting, which include nutrition and metabolic support as important components … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 60 publications
(130 reference statements)
0
1
0
Order By: Relevance
“…Supplemental PN (SPN) refers to a mixed nutritional support method, in which part of the energy and protein is supplemented by PN when EN is insufficient ( 8 , 9 ). Studies have found that reasonable SPN can meet the energy and protein needs of critically ill patients, promote protein synthesis, adjust nitrogen balance, improve nutritional status, and even reduce complications and improve prognosis ( 10 ).…”
Section: Introductionmentioning
confidence: 99%
“…Supplemental PN (SPN) refers to a mixed nutritional support method, in which part of the energy and protein is supplemented by PN when EN is insufficient ( 8 , 9 ). Studies have found that reasonable SPN can meet the energy and protein needs of critically ill patients, promote protein synthesis, adjust nitrogen balance, improve nutritional status, and even reduce complications and improve prognosis ( 10 ).…”
Section: Introductionmentioning
confidence: 99%